A simple protocol to evaluate nitrogen utilisation in Saccharomyces cerevisiae - Stella, Carlos A. (2000)
The present article describes a simple protocol that allows the study of nitrogen source utilisation by cells and its relation with cellular growth. The assay can be performed using the minimum of laboratory equipment.